Respuestas

2012-06-28T19:26:56+02:00

siendo el perimetro   P    un lado  mide p/3 el otro  p/5 y el otro  7  solo se  +  y  se =  al P  sale  15u

 

2012-06-28T19:44:20+02:00

P = a+b+c                          P= perimetro

a= P/3

b= P/5

c= 7      

 

Reemplazamos en nuestra ecuacion de perimetro.... P = (p/3) + (p/5) + 7

                                                                              P - (p/3) - (p/5) = 7

                                                                              P = 15